Effect of Williamson parameter on Cu-water Williamson nanofluid over a vertical plate. (October 2022) - Loganathan, P.; Sangeetha, S.
Abstract: The objective of this study is to analyze the augmentation of thermal conductivity and mass transfer rate over a semi-infinite vertical plate on account of nanoparticles suspended in Williamson fluid. Tiwari and Das model for nanofluids involving infinite shear rate viscosity is used in the current review to explain the heat transfer performance of nanofluids. The finite difference method of an implicit type is used to solve the governing dimensionless equations numerically. Graphical illustrations demonstrate the effects of the Williamson parameter on momentum, energy, and concentration, the behavior of skin friction coefficient and heat, and mass transfer rate. According to the present study, higher values of the Williamson parameter increases the skin friction, heat and mass transfer rate.The visualization of velocity, temperature, and concentration in the contour plots are also depicted. It is observed that Weissenberg number increases the velocity temperature and concentration of fluid flow near the plate significantly.